ANSWER

Step-by-step explanation
We want to find the distance between (-4,-2) and (2,3)
To do that, we apply the formula for distance between two points:
![D=\sqrt[]{(x_2-x_1)^2+(y_2-y_1)^2}](https://img.qammunity.org/2023/formulas/mathematics/college/ak1qelegvclwyfd7a2zhaqxzfglhsosdsg.png)
where (x₁, y₁) and (x₂, y₂) are the two points.
Therefore, the distance between the two points is:
![\begin{gathered} D=\sqrt[]{(2-(-4))^2+(3-(-2))^2} \\ D=\sqrt[]{(2+4)^2+(3+2)^2} \\ D=\sqrt[]{6^2+5^2}=\sqrt[]{36+25} \\ D=\sqrt[]{61} \\ D=7.81 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/vsk3i6bct490c0dkmmhq3s13nh57t5l7aj.png)